Kedudukan Otorita Ibu Kota Nusantara dalam Ketatanegaraan dan Dampaknya terhadap Pengelolaan Keuangan Negara: The Position of Nusantara Capital Authority in The Constitution and Its Impacts on State Financial Management - Supriyonohadi; Nuryuaningdiah, Agnes Pembriarni (SHARE Journal, 2025)
The government has established the relocation of Indonesia’s capital city through Law Number 3 of 2022 concerning the Capital City. It is called as Nusantara. The government also formed the Nusantara Capital Authority (IKN Authority) an institution responsible for managing local governance in the IKN region, including collecting taxes and special levies. This study analyzes the role of the authority within the constitution and how it affects managing state’s finances. This research employs a doctrinal method with a statutory approach. The study's findings indicate that the authority holds the status of a ministry-equivalent institution under the House of Representatives' supervision. This authority has the power to collect special taxes although it is not supervised by The Regional House of Representatives. The power to collect tax does not align with the principle of fiscal decentralization stipulated in the State Finance Law. Under Article 8 of the Law, the collection of IKN special taxes shall be performed by the Minister of Finance to ensure the consolidation of state revenue accountability. Such way of collecting taxes is similar to the United States, where the Internal Revenue Service, which is part of the US Department of Treasury, collects federal taxes.